STUDY OF SOME SUBETHNIC AND GENEALOGICAL GROUPS OF KAZAKHS IN PRE-REVOLUTIONARY RUSSIAN HISTORIOGRAPHY (XVIII – EARLY XX CENTURY) - Apendiyev T. A; Smagulov B; Kozybayeva M. M (Scientific Journal of Pedagogy and Economics, 2019)
In article the analysis of works of the Russian researchers devoted to a research of subethnic and genealogical groups of Kazakhs during a specified period of time is given. The author pays attention to ethnographic features of separate groups of the Kazakh population, in particular, of so-called "shala-Kazakh". Features and factors of formation of the specified groups as a part of Kazakhs are shown. Processes of entry into the structure of the Kazakh people of a part of Karakalpaks, Uzbeks, Kalmyks and other foreign-language groups of the population are considered. The paper also draws attention to the peculiarities of the study by Russian authors of sub-ethnic and genealogical groups of Kazakhs. In particular, we are talking about the appearance of the first special works on individual genealogical groups, for example, tolengut.The author also dwells on the assessment of the contribution of individual Russian scholars to the study of the indicated topic.